Self Control and Intertemporal Choice: Evidence from Glucose and Depletion Interventions - Michael A. Kuhn; Peter Kuhn; Marie Claire Villeval (Center for Economic Studies and ifo Institute (CESifo), 2014)
Recent developments in economic theory model intertemporal choice decisions as problems of restraining one's natural impulse to consume today. We use interventions that have been shown in the psychology literature to affect impulse control to examine whether this is indeed the case for laboratory elicitations of time preference. In other words, is savings behavior affected by manipulations of willpower? Our results are mixed, with one widely used willpower-reducing intervention increasing subjects' savings, and with evidence of a substantial placebo effects with respect to another intervention based on sugared beverage consumption. Since all our treatment effects which are substantial in magnitude are driven by increases in the intertemporal substitution elasticity (i.e. greater sensitivity to high prices), we suspect that the primary mechanism behind them is an increase in subjects' attention to the decision, rather than their ability to resist the temptation to get money sooner.
Keywords: C91; D90; 330; time preferences; self-control; depletion; sucrose; experiment